A binary all-nanoporous composite membrane constructed via vapor phase transformation for high-permeance gas separation. Issue 23 (11th October 2021) - Bu, Mengqi; Feng, Yang; Li, Qingxun; Wang, Yiran; Feng, Shou; Zhang, Kai; Jiang, Yujie; Fan, Lili; Kang, Zixi; Sun, Daofeng
Abstract : A COF with a large pore size was incorporated into a MOF matrix to construct an all-nanoporous composite membrane for high-permeance gas separation. Abstract : Metal–organic framework (MOF) membranes with an ultra-small pore size (<4 Å) have shown great prospects in the highly selective separation of small gas molecules such as hydrogen, but their narrow channels may result in a low gas permeance. To improve the gas permeance of ultra-microporous MOF membranes, a stable covalent organic framework (COF) with large and uniform pores is doped to construct a binary COF/MOF all-nanoporous composite (ANC) membrane, equivalent to reducing the effective membrane thickness but avoiding the challenging ultra-thin membrane preparation. The COF synthesized by ball milling is combined with a metal gel to form a precursor membrane, which was then transformed to a COF/MOF ANC membrane by treatment with the MOF ligand vapor. A very small amount of solvent has been applied, offering an environmentally-friendly preparation process. Compared with the pristine MOF membrane, the COF/MOF ANC membranes possess a highly improved gas permeance from 22 GPU to 551 GPU with a slight sacrifice of selectivity; this introduces a new strategy to optimize the separation performance of MOF membranes.